If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 10 = 5 Reorder the terms: 10 + -1x = 5 Solving 10 + -1x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 5 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 5 + -10 -1x = 5 + -10 Combine like terms: 5 + -10 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| (-4y-2)+(2y-7)= | | 7(a+5)=79.8 | | 51.2=9c-1 | | 7p=68.6 | | 2(d-8)=2 | | 3(a+3)=27 | | 3=2c-1 | | 9e-1=62 | | 5x+2/5=21/15 | | 8x=3x | | 9d+8=3d+20 | | 2(1/3)+2/3 | | 2x(x-1)=3x-28 | | 7x^2-14x-23=6x^2-23x+29 | | -72-10x=130-31x | | x-1/3=6 | | 8y+3=3Y+4y | | 9k=81 | | 6-10x=30-34x | | 124-4x=4x+26 | | 11^1/2*11^3 | | -35-(-7)= | | (9)^3/2 | | (-10)+(-5)= | | (16)^3/4 | | (-84/5)*(-52/3) | | 26x^2-27x^2= | | 0.3x+4.25=9.1-0.33x | | 68-4x=14x+16 | | 2x^4-5x-12=0 | | 3d=2d-2 | | 20a-8f= |